The Relationship between Some Inflammatory Proteins and Autoantibodies in Diabetic Type II Patients - Salih, Asmaa M; Mohamood, Aysar E; Al-Ubaidi, Alia E M; Jawad, Adnan Hadi (Al-Nahrain Journal of Science, 2013)
Diabetes mellitus type II considers as inflammatory disease, which it associated with increasing level of sensitive inflammatory proteins, Adult patients with DM type II may progress a slowly failure of Beta-cells. Some patients show an autoimmune nature of the disease, our Present study aimed toevaluatethe relationship between autoantibodies which includes islet cell antibodies and insulin autoantibodies along with some inflammatory sensitive proteins like Ceruleplasminand Transferrinin type II diabetes mellitus of recent onset disease in an Iraqi population. A total of 50 patients with type II diabetes mellitus were studied as well as 31 control healthy individuals,the individuals in each group were divided into sub groups according to the presence of autoantibodies. The present study tested the presence of both autoantibodies against islet cells in both patients and control groups, the results show the presence of at least one type of autoantibodies and the coexistence of two types of autoantibodies where observed in three patients, therefore, the individuals in each group were divided into sub groups according to the presence of autoantibodies. Serum Ceruloplasmin level showed significant increasing between negative patients group and negative control group, but this increasing is non-significant between positive patients group and positive control group. Positive control group showed significant increasing in serum Ceruloplasmin level compared to negative control group and thatincreasing made serum Ceruloplasmin level in positive control group closely related to its level in positive patient group, while positive patient group showednon- significant increasing compare to negative patient group. Transferrin showed non-significant decreasing level in patient group compared with control for both groups of autoantibody. Present results may refer to inflammatory aspects of disease which associated with autoimmunity markers, moreover, the presence of autoantibodies increased the serum Ceruloplasmin level and decreased level of Transferrin even in healthy individuals. Present conclusion could help in the diagnosis and provide protection from developing disease.